Creative's commons nurturing the local creative economy through a visual arts and animation center - Pintor, Neal Armand S. (College of Architecture, University of the Philippines Diliman, 2025)
The Philippines possesses 40-years-worth of knowledge and skills in the animation industry, but has failed to progress up the global creative economy value chain. While a growing number of local schools have opened animation programs; the industry is bottlenecked by the lack of a cohesive employment pipeline and creative intellectual property. The study "Creatives' Commons: Nurturing the Local Creative Economy through a Visual Arts and Animation Center" explores a shared service visual art center that stimulates the common creative sensibilities between enthusiasts, students, and professionals in the illustration, comics, and animation industry; and bridges it with their social preferences. Data on the different visual creatives' conceptualization, production, and collaboration processes were obtained using qualitative research methods which include community engagement, surveys,interviews, observations; and is synthesized into the design of a commercial and civic space for the arts. By looking into the intersection of socially-interactive, creativity-stimulating design, and the nuanced experiences of students, and visual artists, who live with and without access to studio employment and facilities; this study introduces a cohesive visual arts education and production facility in Naga City, home of one of the country's pioneer animation schools. The center functions as a preference-responsive third place for students and hobbyists to hone their craft, a professional facility to accelerate original IP creative production, and an urban landmark that opens more creative work opportunities outside of Metro Manila.